Factores de éxito en el posicionamiento de una App de servicios para el hogar - Suarez Figueroa, Luis Alberto (2021)
The objective of the research was to know if there was a correlation between the chosen success factors such as: branding, customer experience and advertising with respect to the positioning of a home services App. The research has a quantitative approach making use of the survey as the chosen instrument to obtain the necessary information that was later processed through a statistical program called SPSS. The data were analyzed using the corresponding test statistic, this being the case of the use of the Spearman correlation test, with which the hypothesis could be contrasted and finally conclusions drawn. In the data collection, surveys were applied to 384 people in zones 6 and 7 of Lima in a random way and the SPSS program was used for the validation of the hypotheses and data analysis. Sampling is non-probabilistic for convenience, since it is easier, faster and less expensive to develop the research. With the results obtained, it was possible to identify that the chosen variables were correlated with the dependent variable, however, each one had a different degree of association with respect to the dependent variable where it was finally obtained that the advertising variable was correlated or associated with greater force to the variable positioning followed by branding and customer experience.